Tuberculosis in Aboriginal Canadians. Issue 2 (3rd April 2000) - Hoeppner, Vernon H; Marciniuk, Darcy D
Abstract : Endemic tuberculosis (TB) was almost certainly present in Canadian aboriginal people (aboriginal Canadians denotes status Indians, Inuit, nonstatus Indians and metis as reported by Statistics Canada) before the Old World traders arrived. However, the social changes that resulted from contact with these traders created the conditions that converted endemic TB into epidemic TB. The incidence of TB varied inversely with the time interval from this cultural collision, which began on the east coast in the 16th century and ended in the Northern Territories in the 20th century. This relatively recent epidemic explains why the disease is more frequent in aboriginal children than in Canadian-born nonaboriginal people. Treatment plans must account for the socioeconomic conditions and cultural characteristics of the aboriginal people, especially healing models and language. Prevention includes bacillus Calmette-Guerin vaccination and chemoprophylaxis, and must account for community conditions, such as rates of suicide, which have exceeded the rate of TB. The control of TB requires a centralized program with specifically directed funding. It must include a program that works in partnership with aboriginal communities.